2008
DOI: 10.5194/bgd-5-661-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centennial black carbon turnover observed in a Russian steppe soil

Abstract: Abstract. Black carbon (BC), from incomplete combustion of fuels and biomass, has been considered highly recalcitrant and a substantial sink for carbon dioxide. Recent studies have shown that BC can be degraded. We use soils sampled 100 years apart in a Russian steppe preserve to generate the first whole-profile estimate of BC stocks and turnover in the field. BC stocks (initially 2.5 kg m-2) decreased 25% with cessation of biomass burning. BC turnover in the soil was 293 y (best estimate; range 212–541 y), mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Nonetheless, the high uncertainty of the fitting curve does not enable predicting the decomposed amounts over periods longer than a few years. This finding is consistent with Hammes et al (2008), who found that the proportions of less-condensed biochar C decreased when compared the quality of BPCA between archived and modern soil samples in a Russian steppe. In contrast to the amounts, the decomposition rate of biochar showed a clear decrease pattern with experimental duration (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, the high uncertainty of the fitting curve does not enable predicting the decomposed amounts over periods longer than a few years. This finding is consistent with Hammes et al (2008), who found that the proportions of less-condensed biochar C decreased when compared the quality of BPCA between archived and modern soil samples in a Russian steppe. In contrast to the amounts, the decomposition rate of biochar showed a clear decrease pattern with experimental duration (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consequently, the available field observations do not support the standpoint that biochar can persist in soils for several thousands of years. Furthermore, current analyses of forest soils in northern Europe and Russian steppes also indicated a centennial-scale turnover of biochar (Hammes et al, 2008;Ohlson et al, 2009). Serious caution is therefore needed when extrapolating results of biochar decomposition from incubation studies to real field conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated MRTs of pyrogenic materials (including biochar) are very variable, ranging from decades or centuries (e.g. Bird et al, 1999;Hammes et al, 2008;Steinbeiss et al, 2009) to millennia (e.g. Thevenon et al, 2010;.…”
Section: Pyc Degradationmentioning
confidence: 99%
“…Long-term mean residence time (MRT) of biochar in two different savanna regions were estimated up to 1300 and 2600 years (Lehmann et al, 2008). In contrast, Hammes, Torn, Lapenas, and Schmidt (2008) calculated a turnover time of biochar in a Russian steppe soil of only 293 years and Bird, Moyo, Veenendaal, Lloyd, & Frost, (1999) report a half-life of charcoal in savannah soil of <100 years. A meta-analysis by Wang et al, (2016) revealed that the decomposed amount of biochar increased with experimental duration, but the decomposition rate decreased with time and MRT of biochar was estimated to 556 AE 483 years.…”
mentioning
confidence: 99%